Challenges in diagnostic testing of nephritic factors - Michels, Marloes A. H. M.; Volokhina, Elena B.; van de Kar, Nicole C. A. J.; van den Heuvel, Lambertus P.W. J. (Frontiers in Immunology, 2022)
Nephritic factors (NeFs) are autoantibodies promoting the activity of the central enzymes of the complement cascade, an important first line of defense of our innate immune system. NeFs stabilize the complement convertase complexes and prevent their natural and regulator-mediated decay. They are mostly associated with rare complement-mediated kidney disorders, in particular with C3 glomerulopathy and related diseases. Although these autoantibodies were already described more than 50 years ago, measuring NeFs for diagnostic purposes remains difficult, and this also complicates our understanding of their clinical associations. In this review, we address the multifactorial challenges of NeF diagnostics. We describe the diseases NeFs are associated with, the heterogenic mechanisms of action of different NeF types, the different methods available in laboratories used for their detection, and efforts for standardization. Finally, we discuss the importance of proper NeF diagnostics for understanding the clinical impact of these autoantibodies in disease pathophysiology and for considering future complement-directed therapy.